2001
DOI: 10.1111/j.1572-0241.2001.03804.x
|View full text |Cite
|
Sign up to set email alerts
|

Colonic Motility Abnormality in Patients With Irritable Bowel Syndrome Exhibiting Abdominal Pain and Diarrhea

Abstract: The dysmotility in this subset of IBS patients was characterized by significantly increased occurrences of powerful HAPCs that paralleled rapid colon transit and were accompanied by abdominal pain. Thus, it is suggested that this powerful contraction is one of the causes of abdominal pain. The action of CCK-8 seems to be mediated via the colon enteric nervous system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
97
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(108 citation statements)
references
References 17 publications
6
97
0
3
Order By: Relevance
“…The most prevalent forms of motility-related diarrheas are autonomic neuropathy 106 or IBS-D, associated with either accelerated colonic transit 107 or increased numbers of high-amplitude propagated contractions. 108 …”
Section: Secretory or Osmotic Diarrheamentioning
confidence: 99%
“…The most prevalent forms of motility-related diarrheas are autonomic neuropathy 106 or IBS-D, associated with either accelerated colonic transit 107 or increased numbers of high-amplitude propagated contractions. 108 …”
Section: Secretory or Osmotic Diarrheamentioning
confidence: 99%
“…Although motor abnormalities of the large bowel have been described in both conditions [3, 4, 5, 6], especially for IBS, unequivocal data have not been reported consistently. Recent evidence, however, seems to suggest that an abnormal colonic motility may actually be documented in IBS patients [7, 8, 9, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…CCK-33 can decompose several fractions, one of which is CCK-8. It has been reported that the use of CCK-8 intravenously can lead to abdominal pain in human [6]. As we all know, CCK can cause gastrointestinal smooth muscle contraction and improve gastrointestinal motility after binding the CCK receptor.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, enhanced visceral perception is considered to be important as it has been reported that up to 94% of patients are hypersensitive to rectal balloon distension [5]. There is also evidence pointing to altered gut motility in IBS [6]. …”
Section: Introductionmentioning
confidence: 99%